Gestión administrativa y su incidencia en la recuperación de cartera vencida del camposanto colina de los recuerdos, Quevedo, año 2023. - Tigua Bejarano, Evelyn Maribel (2025)
This project analyzes administrative management and its influence on the recovery of overdue loans at the Colina de los Recuerdos Cemetery, located in Quevedo. The research arose in response to the increase in delinquency, which affects the institution's financial sustainability. Its overall objective is to evaluate the administrative factors that influence the recovery of overdue loans, identifying deficiencies in collection processes and proposing improvement strategies. The methodology used is quantitative, descriptive, and exploratory, applying surveys to administrative staff and documentary analysis of financial records. The most relevant results indicate that 60% of staff consider the economic crisis to have been the main factor in delinquency, while 40% point to deficiencies in collection management, such as a lack of timely follow-up and ineffective communication with clients. Furthermore, it was found that 80% of debt records are updated monthly, but follow-up with delinquent clients is insufficient. Based on these findings, an administrative management model was designed that integrates five key components: planning, organization, direction, control, and evaluation. The implementation of more flexible collection strategies, portfolio segmentation based on risk level, and the use of automated technological tools are recommended. In conclusion, the implementation of this model will reduce the overdue portfolio by at least 30% in the first year, improving the financial stability of the Colina de los Recuerdos Cemetery and optimizing its economic indicators.